REDESAIN BANGUNAN BAGI DAN BANGUNAN SADAP DI DAERAH IRIGASI BENDUNG AIR KEMUMU KABUPATEN BENGKULU UTARA - Romah, Septi Kurnia Hayati; Besperi, Besperi; Gunawan, Gusta (Inersia: Jurnal Teknik Sipil, 2017)
Air Kemumu weir in Kemumu village subdistrict of Kecamatan Arma Jaya Bengkulu Utara  Regency, is one of the weir which has irrigation canal and irrigation construction in its system. This research is aimed to plan the canal dimension, divider, and reservoir construction based on 5, 50, and 100 years periodic flow in Kemumu weir irrigation area of Bengkulu Utara. Observation and measurement were done directly in that area in order to find out the dimensionand the problem. Research method that is used in this research is done by counting down the rainfall data by using algebra average method. The primary data are taken from the speed of water flow in canal, canal dimension, and construction dimension. The expected result of rainfall measurement that can complete pre-requirement is Gumbel method type 1. The measurement of the flow is using rational method for any types of periodic flow. The result of this research is finding the final hydrolysis measurement for the secondary BW.1 and tertiary BS 2A canal are 0,52m and 0,35m for the base width BW.1 and BS 2A. The measurement for the canal design based on periodic flow for BW.1 and BS 2A in Q5, Q50, and Q100 are 2,14m, 2,92m,3,14m, 1,74m, 2,17m, and 2,34m. Thetop width (b) measurement of the divider BW.1 and reservoir BS 2A construction are 0,44m and 0,24m. The measurement of its width in Q5, Q50, and Q100 are 1,78m, 2,44m, 2,60m, 1,50m, 2,20m, and 2,34 m.